PENGARUH FAKTOR SOSIAL, EKONOMI DAN DEMOGRAFI TERHADAP KSEJAHTERAAN LANSIA DI KOTA DENPASAR - Viryamitha, Made Dhea; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Elderly people have the right to get the same welfare as other residents, so they need understanding of the factors that affect the welfare of the elderly in terms of socio-economic and demographic aspects. The purpose of this study is 1) To analyze the effect of simultaneous education level, marital status, age, income and sex on the welfare of the elderly in Denpasar City. 2) To analyze the effect of education level, marital status, age, income and gender partially on the welfare of the elderly in Denpasar City. The research method used is multiple linear regression with a sample of 100 elderly people. The data used are primary data obtained through in-depth interviews with respondents. The results of this study are, 1) The level of education, marital status, age, income and gender  simultaneous and significant effect on the welfare of the elderly in Denpasar City. 2) The level of education, income, and marital status significant positive effect partially on the welfare of the elderly in the city of Denpasar, Age significant positive effect not partially on the welfare elderly in city of Denpasar, the gender does’t have significant negative effect.   Keywords: education level, marital status, age, income, gender, elderly welfare.